Comparative activity pattern and feeding behaviour of Capped Langur (Trachypithecus pileatus) and Rhesus Macaque (Macaca mulatta) in Madhupur National Park of Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2017)
Comparative activity pattern and feeding behaviour of Capped Langur (Trachypithecus pileatus) and Rhesus Macaque (Macaca mulatta) were studied in Madhupur National Park of Bangladesh from September 2015 to September 2016. Scan sampling method with 5 minutes interval was followed in the field. The Capped Langur spent 42% of the day time in feeding, 45% in resting, 6% in moving, 4% in playing, 2% in grooming and 1% in breeding, whereas the Rhesus Macaque spent 24% of the day time in feeding, 26% in resting, 30% in moving, 15% in playing, 4% in grooming and 1% in breeding. The Capped Langur spent comparatively more (7.25%) time in feeding than the Rhesus Macaque. Seasonal variation in feeding of the Capped Langur is more obvious than that in the Rhesus Macaque. Both species started their feeding activities early in the morning and stopped at late afternoon. Diet of the Capped Langur comprises of plant food (94%), animal food (3%), water (1%) and food offered by men (2%), and diet of the Rhesus Macaque comprises of plant food (79%), animal food (4%), soil (1%), water (2%) and food offered by men (14%). Both are mainly vegetarian but fed on varieties of food. It was found that the Capped Langur is primarily folivorous (48%) and the Rhesus Macaque is primarily frugivorous (55%). The Capped Langur fed on a total of 51 species of plant under 28 families and Rhesus Macaque fed on 38 species of plant under 18 families. The Capped Langur consumed more natural food (98%) than that of Rhesus Macaque (86%); the rest were food offered by men. The day ranges of Capped Langur and Rhesus Macaque were 400 metres and 550 metres, respectively. No notable conflict between Capped Langur and Rhesus Macaque was observed while feeding.Jahangirnagar University J. Biol. Sci. 6(1): 1-12, 2017 (June)